Veni vidi vici: vilified visuality of Indonesian PATIs - Badrul Redzuan Abu Hassan, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Much of what we know about the world is informed visually through the prosthetic lens of the photographer. An important post-colonial and cultural studies scholarship today is about investigating visual culture, particularly on the relationship between photography and cultural identities of 'the Other'. By way of 'imperious' and 'colonial' guises, photography may be effectively by the ruling elite to inform the dominant polity or society about the cultural identity of its 'Other'. This study argues that certain photographic representations of Indonesian illegal migrants or PATIs (lit. Pendatang Asing Tanpa Izin) by Malaysian print media during the period of their amnesty from the Malaysian government and their eventual deportation by December 2004, are inherently ideological and unnecessarily manipulative. However, it also argues that visual literacy can be employed to deconstruct and raise our awareness of such discursive production which operates against a benevolent construction of the Indonesian PATIs.